Studi Kelayakan Implementasi Program Sekolah Ramah Anak Untuk Meningkatkan Kualitas Pendidikan Dasar - Sakinah, Khairunnisa; Fahmara Ageela; Gusmaneli (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2024)
Child-Friendly School (SRA) is an educational concept aimed at creating a safe, comfortable, and supportive learning environment for children's holistic development. Focusing on protection, participation, and development, SRA contributes to improving the quality of basic education in Indonesia. This program is not only academically oriented but also emphasizes students' emotional and social well-being. The implementation of SRA faces challenges such as limited funding, lack of teacher training, and parental support. To address these challenges, strategic recommendations are needed, including increased education budget allocation, ongoing teacher training, and strengthening partnerships between schools, parents, and communities. With these measures, SRA is expected to have a significant positive impact on student development and the quality of education in Indonesia.